2021
DOI: 10.1080/14029251.2014.975531
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Ermakov-Painlevé IV Systems

Abstract: Ermakov-Painlevé IV coupled systems are introduced and associated Ermakov-type invariants isolated. These invariants are used to obtain systematic reduction of the system in terms of the canonical Painlevé IV equation. The procedure is applied to a Ermakov-Painlevé IV symmetry reduction of a coupled derivative resonant nonlinear Schrödinger triad incorporating de Broglie-Bohm potential terms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 58 publications
(57 reference statements)
0
7
0
Order By: Relevance
“…Our findings reveals the importance of future studies devoted to construct analytical/approximated solutions of the Gambier equations in order to better understand the behaviour of Gambier inspired cosmological models. Even though, the role of the Ermakov-Pinney equation in FLRW cosmology is well known in the literature, here we have explored the role of various generalizations of Pinney equation, as formulated by [26][27][28], in 2+1-dimensional FLRW cosmology. This raises an important issue regarding the existence of a systematic relation between integrable class of 1+1-ODEs and FLRW cosmology and clearly, demands further investigation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings reveals the importance of future studies devoted to construct analytical/approximated solutions of the Gambier equations in order to better understand the behaviour of Gambier inspired cosmological models. Even though, the role of the Ermakov-Pinney equation in FLRW cosmology is well known in the literature, here we have explored the role of various generalizations of Pinney equation, as formulated by [26][27][28], in 2+1-dimensional FLRW cosmology. This raises an important issue regarding the existence of a systematic relation between integrable class of 1+1-ODEs and FLRW cosmology and clearly, demands further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…He showed that the Ermakov invariants admitted by the hybrid system were key to its systematic reduction in terms of a single component Ermakov-Painlevé II equation which, in turn, may be linked to the integrable Painlevé II equation. Rogers [27] further extended the hybrid family to derive Ermakov-Painlevé IV equation and investigated the connection between the FLRW cosmology of [24] and the generalized Pinney equations derived by Rogers, Schief and Winternitz [28]. We may exploit the underlying Ermakov type invariants of these equations to obtain solutions of the reduced FLRW cosmological equation with scalar field and perfect fluid matter source.…”
Section: Introductionmentioning
confidence: 99%
“…In reference [4] the Painlevé property test was established in the context of equation (1) with arbitrary ǫ i , i = 0, 1. The idea of of generalizing two different Painlevé equations has been explored in the literature in different settings and good examples of such work are [15], [25].…”
Section: Review Of P Iii−v Equations and Their Symmetriesmentioning
confidence: 99%
“…Thus, the only known hybrid solitonic-Ermakov system seems to be that obtained in [54,55] where a 2+1-dimensional Ernst-type system of general relativity as derived in [56], suitably constrained, leads to a novel composition of the integrable 2+1-dimensional sinh-Gordon equation of [30,31] and of a generalised Ermakov-Ray-Reid system. The work of [2,[36][37][38] on Ermakov-Painlevé II systems has recently been augmented by the introduction in [47] of prototype Ermakov-Painlevé IV systems via a symmetry reduction of a coupled derivative resonant NLS triad. Dirichlet type two-point boundary value problems for a single hybrid Ermakov-Painlevé IV equation have been investigated with regard to existence and uniqueness properties in [3].…”
Section: Introductionmentioning
confidence: 99%